1999
DOI: 10.1001/archopht.117.7.917
|View full text |Cite
|
Sign up to set email alerts
|

Serum Autoantibodies to Optic Nerve Head Glycosaminoglycans in Patients With Glaucoma

Abstract: Background: Serum autoantibodies that cross-react with glycosaminoglycans have been proposed to play a significant role in specific tissue injury in patients with systemic autoimmune diseases. Objective: To investigate whether serum immunoreactivity to glycosaminoglycans is present in patients with glau-comawhohaveaberrantserumautoantibodiestoDNA,RNA, nuclear proteins, or retinal proteins, as proteoglycans and their glycosaminoglycan side chains are important components of the optic nerve head and its vasculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
13

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 39 publications
4
87
0
13
Order By: Relevance
“…20 It has also been suggested that serum autoantibodies that crossreact with GAGs around the optic nerve may play a significant role in the development of NTG in some patients with systemic autoimmune diseases. 11 A recent study showed 21 that the immune system plays a key role in an animal's ability to resist the damaging consequences of an increase in IOP. Rats deprived of T cells were found to be more prone to IOP-induced retinal ganglion cell (RGC) loss than rats with normal T-cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has also been suggested that serum autoantibodies that crossreact with GAGs around the optic nerve may play a significant role in the development of NTG in some patients with systemic autoimmune diseases. 11 A recent study showed 21 that the immune system plays a key role in an animal's ability to resist the damaging consequences of an increase in IOP. Rats deprived of T cells were found to be more prone to IOP-induced retinal ganglion cell (RGC) loss than rats with normal T-cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…2 This study found a statistically significant increase in autoantibodies to extractable nuclear antigens (ENA) and serum monoclonal proteins in NTG, but failed to show a statistically significant increase in antinuclear antibodies. Other workers have identified immunoglobulin deposition in the retina in NTG, 10 whereas numerous elevated serum autoantibody titres have also been demonstrated, for example, to optic nerve head glycosaminoglycans (GAGs), 11 to gammaenolase, 12 to retinal antigens (including rhodopsin 13 ), to heat-shock proteins, 14 and to glutathione S-transferase.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed antibodies against, e.g., heat shock proteins [99], g-enolase [100], GST [101], glycosaminoglycans [102], and a-fodrin [80]. Studies of our group revealed significant differences in antibody patterns against ocular antigens in sera of glaucoma patients in comparison to healthy controls [80,[103][104][105][106].…”
Section: Glaucomamentioning
confidence: 97%
“…Feedback loops regulated by astrocytes in microglia work in reverse too: Microglia can activate the Nrf2-ARE (anti-oxidant response element) in astrocytes and change the redox level there. An autoimmune component to glaucomatous optic neuropathy has emerged from observations of serum autoantibodies against proteoglycans in open-angle glaucoma patients (Tezel et al, 1999), and against heat shock proteins (hsp) hsp27 and hsp60 (Wax et al, 2008) in patients with normal tension glaucoma (NTG). Microglia have a complex, context-dependent role in autoimmunity.…”
Section: Microgliamentioning
confidence: 99%
“…As demonstrated in the retina (see Figure 1), glia overexpress proteoglycans during gliosis in glaucoma. Serum autoantibodies obtained from patients with normal tension glaucoma and those with increased IOP bind to chondroitin sulfate and heparan sulfate glycosaminoglycans, proteins upregulated in the optic nerve head of glaucoma patient tissue (Tezel et al, 1999). However, chondroitin sulfate proteoglycan 4 (CSPG4) and CSPG1 (aggrecan) mRNA stood out on one ONH astrocyte microarray for being downregulated 35-fold and 29-fold, respectively in glaucoma patients (Hernandez et al, 2002).…”
Section: Onh Astrocytesmentioning
confidence: 99%